Multi-core and single-core Raspberry Pi microprocessor’s - Sainuddin, Nurulidayu; Mohd Sultan, Juwita; Azuani, Mohamed (Wydawnictwo SIGMA-NOT, 2023)
A multi-core processor is defined as an integrated chip that consists of two or more processors used for system performance enhancement, speed improvement, and multitasking performances. They collaborate to execute instructions faster than the single-core processor. Hence, this paper provides an overview of the evolution of the processor architecture and analysis of the multi-core processor's performance compared to the single-core processor. It highlights the difference in Central Processing Unit speed, memory bandwidth, power consumption, and the thermal effect on the CPU speed during throttling for single-core ARM11 with Broadcom BCM2835 and a quad-core Cortex-A72 with Broadcom BCM2711B0. Experimental results show that Cortex-A72 has a memory bandwidth of 29 times larger than the ARM11. The CPU speed benchmark indicates that Cortex-A72 is significantly faster and responds to the thermal throttling better than the ARM11 processor. However, as Cortex-A72 has more processing power, it has drawn more power than the ARM11 processor.